Preparation and characterization of novel hybrid of bio-assisted mineralized Zn-Al layered double hydroxides using chitosan as a template - Depan, Dilip; Singh, Raj Pal (Journal of Applied Polymer Science, 2010)
The purpose of this study was to prepare and characterize a novel nanohybrid prepared from the template-assisted mineralization of Zn-Al Layered Double Hydroxide (LDH) onto the surface of Chitosan (CSI), with an emphasis on morphology, biocompatibitity, and its use as an efficient drug carrier agent. The as prepared LDH is highly crystalline, with platelet-like morphology and curved tactoids when nucleated onto the surface of CSI. Our results indicate that the -OH and -NH functional moieties on CSI can direct an ordered structure of LDH, due to the electrostatic interaction between biopolymer and inorganic lamellae. We have been successful to intercalate an anti-inflammatory drug, Sodium Ibuprofen (Ibu), into LDH, through conventional coprecipitation method. LDHs are endowed with great potential for delivery vector because their stacked layers lead to safe reservation of biofunctional molecules or genes, and their ion exchangeability and solubility in acidic media (pH < 4) give rise to the controlled release of drug molecules. According to the cell-growth studies, LDHs are found as cell viable up to the concentration of 500 mu g/mL. This study reveals that LDH not only plays a role of a biocompatible-delivery matrix but also facilitates a significant increase in the delivery efficiency. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115:3636-3644,2010
Keywords: bio-assisted mineralization; cell-growth studies; Chitosan; drug delivery systems; layered double hydroxides